1995
DOI: 10.1177/000841749506200104
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapists as Case Managers: Responding to Current Approaches to Community Mental Health Service Delivery

Abstract: Case management has been identified as an effective approach to service delivery which can assist persons with severe psychiatric disabilities to live in the community. The conceptualization and development of case management services have been the focus of much discussion. Occupational therapists are attempting to define their role in relation to case management. The purpose of this paper is to explore the relationship between occupational therapy and the case management approach to service delivery. The case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…This ambiguity is mirrored in the field in general. Only recently, has the role of case manager been discussed in the literature as a legitimate role for occupational therapists in community practice (American Occupational Therapy Association Statement, 1991; Krupa & Clark, 1995). As the literature grows, roles in enabling occupations may become better understood and accepted within the profession.…”
Section: Personal and Professional Growthmentioning
confidence: 99%
“…This ambiguity is mirrored in the field in general. Only recently, has the role of case manager been discussed in the literature as a legitimate role for occupational therapists in community practice (American Occupational Therapy Association Statement, 1991; Krupa & Clark, 1995). As the literature grows, roles in enabling occupations may become better understood and accepted within the profession.…”
Section: Personal and Professional Growthmentioning
confidence: 99%
“…' (p197) As in the Australian literature, there is reference to innovative methods of providing services for those with mental health problems. Krupa and Clark (1995) outlined the case management approach and its relationship to occupational therapy. In their opinion the similarities between them relate to adopting an holistic perspective, promoting independence and emphasising function rather than illness.…”
Section: Association Of Occupational Therapists (1989) As a Position mentioning
confidence: 99%
“…The finding does appear to agree with the report of Gardner and McCoppin (1988), who have argued that physiotherapy has attained a greater degree of professional independence and status than other allied health professional groups. In addition, recent research in occupational therapy suggests that this professional group is still concerned with defining their role (Krupa & Clark 1995). No significant difference was obtained between speech pathologists, occupational therapists and physiotherapists with regard to interactions between members of their own profession and other health professionals.…”
Section: Differences In Professional Relationships and Work Role: Permentioning
confidence: 93%
“…These differences may have important planning implications, in that it has been suggested that low professional status and lack of control over working conditions may motivate hospital nurses to enter practice in the community and thereby expand their roles (Akroyd et al 1994). Most studies of workplace roles and professional interactions among health personnel do not compare professional groups, although literature within each profession does consider these issues (for example, Krupa & Clark 1995;Raz et al 1991). Given the significant differences within the nursing profession across workplace settings, it is likely that important interprofessional differences exist between allied health professional groups.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation